2010
DOI: 10.1108/17410381011046616
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of lean Six Sigma in financial services organizations

Abstract: PurposeThe purpose of this paper is to obtain pertinent information pertaining to benefits accomplished, main difficulties felt, and key lessons learned in the implementation of lean Six Sigma (LSS), which are likely to be helpful to financial services organizations wanting to implement the same tool.Design/methodology/approachThis paper reports the results of a case study from a financial services organization which has begun the implementation of LSS methodologies ten years ago, in the pursuit of service exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 17 publications
(27 reference statements)
4
138
0
3
Order By: Relevance
“…The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011). In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation.…”
Section: Research and Practical Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011). In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation.…”
Section: Research and Practical Implicationssupporting
confidence: 77%
“…Lean Six Sigma (LSS) is a business improvement strategy that has flourished over the last decade because of its promise of enhanced business performance and market capability. LSS has evolved through the combination of Lean and Six Sigma, both recognised as leading total quality management (TQM) tools for performance improvement in organisations with a proper infrastructure built on leadership and change culture (Dora and Gellynck, 2015;Assarlind et al, 2013;Wang and Chen, 2012;Choi et al, 2012;Hilton and Sohal, 2012;Atmaca and Girenes, 2013;Lee et al, 2011;Delgado et al, 2010;Dahlgaard and Dahlgaard-Park, 2006;McAdam and Lafferty, 2004). LSS is now regarded as one of the most effective and disciplined business transformation initiatives available in strategic operations management as well as an effective top-down methodology for improving quality in both the manufacturing and service small-and medium-sized enterprise (SMEs) and their larger counterparts (Kanpp, 2015;Isa and Usmen, 2015, Bhat et al, 2014, Algassem et al, 2014Biranvand and Khasseh, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a multiple case-study deployed comparison of events and data across cases mitigates usual case research risks, augments external validity and provides opportunity for bringing more generic conclusions (Voss et al, 2002;Nonthaleerak and Hendry, 2008). Furthermore, a qualitative approach was adopted since it is more suitable for capturing complex relationships (Delgado et al, 2010), for exploring the impact of different institutional and contextual factors on operations management tools and techniques (Psychogios and Priporas, 2007) and reconciles complexity, details and context (Mangen, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, managementoriented factors include the integrating L6σ with business strategy (Lubowe and Blitz, 2008;Fornari and Maszle, 2004;Antony et al, 2007;Kamensky, 2008), selection and management of the right project Laosirihongthong et al, 2006;Ladhar, 2007;Breyfogle, 2008), and customer satisfaction (Antony et al, 2003;Antony et al, 2007;Andel 2007;Lubowe and Blitz, 2008). The people-oriented factors include Committed leadership (Laosirihongthong et al, 2006;Maleyeff, 2007;Stuenkel and Faulkner, 2009;Carleysmith et al, 2009;Ladhar, 2007), Quality-driven Organizational Culture (Furterer and Elshennawy, 2005;Maleyeff, 2007;Lubowe and Blitz, 2008;Koning et al, 2006;Koning et al, 2008;O'Rourke, 2005), training (Anthony et al, 2003;Ladhar, 2007;Caldwell, 2006;Delgado et al, 2010), teamwork (Neuhaus and Guarraia, 2007), and Supportive Technical systems (Kamensky, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Six Sigma DMAIC (Define-Measure-Analyse-Improve-Control) approach has proven itself in a multitude of environments including manufacturing (Kumar & Sosnoski, 2009;Srinivasan, Muthu, Devadasan & Sugumaranl, 2016b) and service sectors (Antony, Antony, Kumar & Cho, 2007;Delgado, Ferreira & Branco, 2010), private and public (Desai & Patel 2009) sectors, governmental (Furterer & Elshennawy, 2005) and non-profit organizations (Cheng & Chang, 2012), and distinct organizations and supply chains (Christopher & Rutherford, 2004;Yang, Choi, Park, Suh & Chae, 2007). Significant benefits have accomplished where DMAIC approach and its' associated tools were connected to an organization's problem solving and improvement activities; including reduction of excess inventory, increase equipment availability, and enhance customer value.…”
Section: Introductionmentioning
confidence: 99%